Impacto das mudanças climáticas em pequenos mamíferos de dois hotspots de biodiversidade - Evaldt, Bruno Henrique de Castro (2021)
Climate change is the unprecedented change in the weather pattern across global and regional scales in a short period due to human activities, and it is expected that it will drive changes in the distribution of species across the globe. Our goal was to analyze how climate change impacts the distribution of species and how species characteristics can affect those changes. To do so, we used the maximum entropy (Maxent) algorithm to model the distribution in the present and four future scenarios for 40 species of non-volant small mammals from the Atlantic Forest and Cerrado biomes. We found that all future scenarios have a significant difference from the present, whereas species will gradually lose more area depending on the scenario, from the most optimistic Representative Concentration Pathway (RCP 2.6) to the most pessimistic (RCP 8.5). Species from the Cerrado will have greater area reduction than species from the Atlantic Forest, and as a consequence, the Cerrado will have proportionally more threatened species than the Atlantic Forest. Species that occur in both biomes will lose proportionally less area than those endemic to the Cerrado but more area than those endemic to the Atlantic Forest. Average elevation will increase in every scenario analyzed and species that occupy higher elevations today will lose more area in the future. We found no relationship between niche breadth or body mass and climate change vulnerability, or differences among clades or locomotion modes. Thus, small mammal species will be negatively impacted by climate change, but the degree of the impact depends on the trajectory of greenhouse gas concentrations. Intrinsic characteristics of the species seem to be less important to predict the vulnerability to climate change than extrinsic characteristics, such as where it occurs, both geographically and in terms of elevation.